Implementasi Supervisi Kelas dalam Upaya Meningkatkan Efektivitas Kinerja Guru - Rosman Farisi (Universitas Mathla'ul Anwar Banten, 2019)
This research focuses on the problem of the low quality of education at Cimarga 1 Junior High School at the moment based on the weakness in the management, organization and development of teachers in the learning process. Efforts to improve the quality of school education must be more focused on improving the quality of human resources, in this case, teachers for students for school residents. In this context, the Principal's Quality Improvement program is very relevant and very strategic, taking into account its functions and roles as leaders and managers of educational institution units at the operational level. This research is a school action research, because the research was conducted to solve the problem of the learning process at school. This study discusses how a learning technique is applied and the expected results can be obtained. The results show a graph of teacher performance improvement in the learning process and the ability of teachers when viewed from the average value of teachers in teaching activities that support the school or in the classroom.